Depiction of woman’s social status in Ancient Cultures and Civilizations in Urdu Feminist Critique - Dr. Shaista Hameed Khan, (Corresponding Author); Dr. Aqsa Sajid; Rao Muhammad Umar (Al-Qanṭara, 2024)
Like other languages, Feminist Critique written in Urdu also depicted many debates about the place and rights associated with women in different cultures and civilizations. Among the ancient civilizations of the world, Greek civilization, Roman civilization, Iraqi civilization, Sumerian civilization, Egyptian civilization, Iranian civilization, China, and even in Arabia, the humiliation of women has been maintained. Women were not considered socially. Their condition was pitiable to such an extent that in Arabia they were buried alive due to fear and honour of famine and in India, they were cremated along with the dead body of their husbands.